Internal variability and model uncertainty components in future hydrometeorological projections: The Alpine Durance basin. Issue 4 (18th April 2014) - Lafaysse, M.; Hingray, B.; Mezghani, A.; Gailhard, J.; Terray, L.
Abstract A multireplicate multimodel ensemble of hydrological simulations covering the 1860–2099 period has been produced for the Upper Durance River basin (French Alps). An original quasi‐ergodic analysis of variance was applied to quantify uncertainties related to General Circulation Models (GCMs), Statistical Downscaling Models (SDMs) and the internal variability of each GCM/SDM simulation chain. For temperature, GCM uncertainty prevails and SDM uncertainty is nonnegligible. Significant warming and in turn significant changes are predicted for evaporation, snow cover and seasonality of discharges. For precipitation, GCM and SDM uncertainty components are of the same order. A high contribution of the large and small‐scale components of internal variability is also obtained, inherited, respectively, from the GCMs and the different replicates of a given SDM. The same applies for annual discharge. The uncertainty in values that could be experienced for any given future period is therefore very high. For both discharge and precipitation, even the sign of future realizations is uncertain at a 90% confidence level. These findings have important implications. Similarly to GCM uncertainty, SDM uncertainty cannot be neglected. The same applies for both components of internal variability. Climate change impact studies based on a single SDM realization are likely to be no more relevant than those based on a single GCM run. They may lead to poor decisions for climate change adaptation.